Peer Assessments in Cooprative Learning Teamworks of Problem-Based Cross-Cultural Translation Classrooms - Mulyanto Mulyanto; Ahmad Heki Sujiatmoko; Amirul Mustofa; Didik Sugeng Widiarto (Journal of Social Science, 2023)
Cooperative Learning (CL) strategy can be the alternative way for leading the students to have the capacity in solving the problems in learning grammar. It is because CL gives the access for the students to have mutual or cooperative working within the groups or team works formed. The students’ mutual or cooperative working can be measured by peer assessments given. The study was aimed at revealing how the students in the groups or team works performed their contributions in solving the problems related to understanding grammar through cross-cultural translation. The study used a quantitative approach within a survey design. There were 50 participants in this study. The research instrument used a questionnaire containing about 16 closed questions distributed via Google form. The result showed that most of the students were initiated to have mutual and cooperative working by being consistent to contribute, feeling a complete sensitivity to others, encouraging others, and having high social attention and care in solving the problems on learning cross-cultural grammar translation. It is recommended that the teachers apply the CL strategy which also gives the access for the students to improve their learning motivations and self confidence through mutual and cooperative working done.